Relations under tension: colombian refugees in quebec (2010)
This article focuses on the relationships developed between Colombians who are settled in Quebec (Canada), as well as on their relationships with their country of origin. According to interviews with Colombian refugees, within this population there isn’t a transnational community, mainly due to the lack of confidence and palpable tension among members. Twenty-seven of the interviewees claim to have perceived in exile a transposition of dynamics associated to the Colombian conflict and therefore marked by the fear to get in contact with people associated with an “adverse camp”